Power quality event source directivity detection based on V-I scatter graph - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
This paper presents a power quality event source directivity detection based on V-I scatter graph. The proposed method is capable to detect both voltage sag and transient power quality event source direction in term of upstream and downstream based on one bus measurement. The V-I scatter graph are plotted based on the RMS voltage and current magnitude at the same instant of time sample onto the voltage versus current graph. Based on the basic principle of power flow, the power quality event source directivity detection are determine by the sector where the plotted VI samples exceeded the voltage and current limits set on the V-I scatter graph. The proposed method is evaluated using simulation model waveforms. The evaluation shows a very promising result of power quality event source direction detection for voltage sag caused by line fault and transient caused by capacitor bank energizing. 2012 IEEE.